Large-conductance Ca2 +-activated K+ channel β1-subunit maintains the contractile phenotype of vascular smooth muscle cells - Wang, Meili; Li, Shuanglei; Liu, Hongshan; Liu, Mingyuan; Zhang, Jin; Wu, Yang; Xiao, Cangsong; Huang, Haixia (Frontiers in Cardiovascular Medicine, 2022)
Background: Vascular smooth muscle cells (VSMCs) phenotype switching is very important during the pathogenesis and progression of vascular diseases. However, it is not well understood how normal VSMCs maintain the differentiated state. The large-conductance Ca2+-activated K+ (BKCa) channels are widely expressed in VSMCs and regulate vascular tone. Nevertheless, there is limited understanding of the role of the BKCa channel in modulation of the VSMC phenotype. Methods and Results: We assessed BKCa channel expression levels in normal and injured carotid arteries from rats of the balloon-injury model. A strong decrease of BKCa-β1 was seen in the injured carotid arteries, accompanied by a parallel decrease of the VSMC contractile markers. BKCa-β1 in primary rat aortic VSMCs was decreased with the increase of passage numbers and the stimulation of platelet-derived growth factor-BB. Conversely, transforming growth factor β upregulated BKCa-β1. Meanwhile, the BKCa-β1 level was positively associated with the levels of VSMC contractile proteins. Intravenous injection of PDGF-BB induced downregulation of BKCa-β1 expression in the carotid arteries. Knockdown of BKCa-β1 favored VSMC dedifferentiation, characterized by altered morphology, abnormal actin fiber organization, decreased contractile proteins expression and reduced contractile ability. Furthermore, the resultant VSMC dedifferentiated phenotype rendered increased proliferation, migration, enhanced inflammatory factors levels, and matrix metalloproteinases activity. Studies using primary cultured aortic VSMCs from human recapitulated key findings. Finally, protein level of BKCa-β1 was reduced in human atherosclerotic arteries. Conclusions: BKCa-β1 is important in the maintenance of the contractile phenotype of VSMCs. As a novel endogenous defender that prevents pathological VSMC phenotype switching, BKCa-β1 may serve as a potential therapeutic target for treating vascular diseases including post-injury restenosis and atherosclerosis.